Fishes of Cocos Island and reef fishes of the Pacific coast of lower Central America: an illustrated guide - Bussing, William A. (2005)
This manual is a companion volume to “Demersal and pelagic inshore fishes of the Pacific coast of lower Central America. An illustrated guide”. That volume treats fishes occurring in habitats on or close to soft substrata, but also includes those inshore pelagic fishes which often appear in fish and shrimp trawl catches, as well as captures made by gill nets, cast nets and other artisanal fishing methods.